Differential efferent projections of GABAergic neurons in the basolateral and central nucleus of amygdala in mice. (6th February 2021) - Liu, Jing; Hu, Tao; Zhang, Meng-Qi; Xu, Chuan-Ying; Yuan, Mao-Yun; Li, Rui-Xi
Highlights: Axonal projections of GABAergic neurons in the BLA distributed to the forebrain. GABAergic neurons in the CEA projected to the forebrain, midbrain and brainstem. Axonal projections of GABAergic neurons in BLA and CEA were mapped and quantified. Abstract: The Basolateral amygdala (BLA) and central nucleus of the amygdala (CEA) have been proved to play a key role in the control of anxiety, stress and fear-related behaviors. BLA is a cortex-like complex consisting of both γ-aminobutyric acidergic (GABAergic) interneurons and glutamatergic neurons. The CEA is a striatum-like output of the amygdala, consisting almost exclusively of GABAergic medium spiny neurons. In this study, we explored the morphology and axonal projections of the GABAergic neurons in BLA and CEA, using conditional anterograde axonal tracing, immunohistochemistry, and VGAT-Cre transgenic mice to further understand their functional roles. We found that the axonal projections of GABAergic neurons from the BLA mainly distributed to the forebrain, whilst GABAergic neurons from the CEA distributed to the forebrain, midbrain and brainstem. In the forebrain, the axonal projections of GABAergic neurons from the BLA projected to the anterior olfactory nucleus, the cerebral cortex, the septum, the striatum, the thalamus, the amygdala and the hippocampus. The axonal projections of GABAergic neurons from the CEA distributed to the nuclei of the prefrontal cortex, the bed nucleus of the stria terminalis, the hypothalamus and the thalamus. In the midbrain and brainstem, the axonal projections of GABAergic neurons from the CEA were found in the periaqueductal gray, the substantia nigra, and the locus coeruleus. These data reveal the neuroanatomical basis for exploring the function of GABAergic neurons in the BLA and CEA, particularly during the processing of fear-related behavior.